Peran Edukasi Kesehatan dalam Pencegahan Penyakit Tidak Menular di Masyarakat: Sebuah Tinjauan Pustaka - Sekar Feni Widiyastuti; Azelia Nusadewiarti (Medula, 2026)
A Non-communicable diseases (NCDs) are the leading cause of global morbidity and mortality, accounting for approximately 71% of all deaths annually, including among the productive-age population. In Indonesia, the prevalence of NCDs such as hypertension, diabetes mellitus, and cardiovascular diseases continues to show a significant upward trend. The main risk factors for NCDs include unhealthy behaviors such as smoking, unhealthy dietary patterns, physical inactivity, and alcohol consumption. From a clinical perspective, controlling these risk factors through behavioral modification is a key strategy to reduce the incidence, progression, and complications of NCDs. Health education plays a crucial role in improving health literacy, including an individual’s ability to understand medical and numerical information related to their health condition. Improved health literacy is associated with better treatment adherence, improved control of clinical parameters such as blood pressure and blood glucose levels, and a reduced risk of long-term complications. Various forms of educational interventions, including healthcare-based services, community-based programs, and digital health technologies, have been proven effective in promoting healthy lifestyle behaviors. However, their implementation still faces several challenges, including low levels of health literacy, sociocultural influences, limited access to information, and suboptimal health system support. Therefore, comprehensive, sustainable, and context-based educational strategies are needed to enhance the effectiveness of both prevention and clinical management of NCDs.